How social start-ups avoid being falling stars when developing social innovation - Battistella, Cinzia; Dangelico, Rosa Maria; Nonino, Fabio; Pessot, Elena (Creativity & Innovation Management, 2021)
The aim of this study is to provide new insights into the social innovation (SI) development process in the context of social start-ups. A multiple case study identifies the issues and mechanisms for social start-ups to develop a social need into a potentially scalable innovation and to validate and scale it up, while avoiding a possible failure. Results show that key challenges faced by social start-ups can be characterized according to the stage of the SI development path. Firstly, social start-ups' failure can be caused by the lack of expertise in social problems and of flexible processes for social ventures creation; secondly, by the lack of awareness of SI benefits and proper resources allocation; and, finally, by a weak understanding of the impact and intangible outcomes of the developed SI in society, while ensuring its economic sustainability. Successfully overcoming these challenges requires social start-ups to put in place the following mechanisms: (1) leveraging a vision and motivations that balance tensions in terms of the radical, economic and cultural aspects of SI; (2) engaging the SI stakeholders in different (and sequential) phases of SI development process; and (3) identifying and adopting the most suitable technological, financial and communication tools in an integrated way.
Keywords: Libre accès; Startup ecosystem

How social start-ups avoid being falling stars when developing social innovation - Battistella, Cinzia; Dangelico, Rosa Maria; Nonino, Fabio; Pessot, Elena (Creativity & Innovation Management, 2021)
The aim of this study is to provide new insights into the social innovation (SI) development process in the context of social start-ups. A multiple case study identifies the issues and mechanisms for social start-ups to develop a social need into a potentially scalable innovation and to validate and scale it up, while avoiding a possible failure. Results show that key challenges faced by social start-ups can be characterized according to the stage of the SI development path. Firstly, social start-ups' failure can be caused by the lack of expertise in social problems and of flexible processes for social ventures creation; secondly, by the lack of awareness of SI benefits and proper resources allocation; and, finally, by a weak understanding of the impact and intangible outcomes of the developed SI in society, while ensuring its economic sustainability. Successfully overcoming these challenges requires social start-ups to put in place the following mechanisms: (1) leveraging a vision and motivations that balance tensions in terms of the radical, economic and cultural aspects of SI; (2) engaging the SI stakeholders in different (and sequential) phases of SI development process; and (3) identifying and adopting the most suitable technological, financial and communication tools in an integrated way.
Keywords: Libre accès; Startup ecosystem